ORAL GRAFT VERSUS HOST DISEASE: A REVIEW - Reddy Lavanya; Reddy Sudhakara Reddy et al. (Journal of University Medical & Dental College, 2016)
ABSTRACT: Graft versus host disease (GVHD or GHz) is a pathological condition in which cells from the transplanted tissue of a donor initiate an immunologic attack on the cells and tissue of the recipient. Generally, transfer of tissues between normal individuals usually results in the recognition and destruction (rejection) of the foreign tissue in a host-versus-graft reaction but immunologically competent cells contained in the transplanted tissue or graft can result in immunologic recognition in the other direction, initiating a graft-versus-host (GVH) reaction. GVHD is a serious, life-threatening disease and it is major complication of bone marrow transplant. The bone marrow is the spongy tissue inside the large bones in the body that makes blood cells and platelets. GVHD may happen in the (short term) acute, or (later after transplantation) chronic, in which case a wider range of organs can be involved.